The European Union Emissions Trading Scheme: should we throw the flagship out with the bathwater?. (29th October 2014) - Branger, Frédéric; Lecuyer, Oskar; Quirion, Philippe
Abstract : The European Union Emissions Trading System (EU ETS), presented as the 'flagship' of European climate policy, is subject to many criticisms from different stakeholders: it neither reduce carbon emissions nor generates enough low‐carbon innovation; it induces competitiveness losses and carbon leakage; its distributional effects are unfair; and, finally; it is susceptible to fraud. We review these criticisms and recognize that abatement is real (though small), innovation is insufficient, competitiveness losses and carbon leakage did not seem to take place, distributional effects have indeed been unfair, and fraud has been important. Some of these problems could have been avoided. They can still be corrected by reforming the ETS through the introduction of price limits and by developing complementary policies, both because the ETS reform may fail and because the ETS cannot address all the relevant market failures. WIREs Clim Change 2015, 6:9–16. doi: 10.1002/wcc.326 This article is categorized under: Climate Economics > Economics of Mitigation Policy and Governance > Multilevel and Transnational Climate Change Governance